when y = -11, 0 + y is equal to -11.
the question is asking us to add 0 to the given value of y. the given value of y is -11, so place -11 into 0 + y and you get 0 + -11. since you are adding zero, you are making no changes to the y value, so it stays at -11.
<em>hope this helps and have a great day!</em>
<h3>C</h3>
f(x) does have an inverse function since it does pass the horizontal line test
Answer:
Its the first choice.
Step-by-step explanation:
an = the nth term. so:
a1 = 6(1) + 1 = 7
a2 = 6(2) + 1 = 13
a3 = 6(3) + 1 = 19
The common difference is 6.
Answer:
wheres the rest of it
Step-by-step explanation:
1500 is minus 1/10 after it is at 1700 thousad